The Birth of a Major Coronal Mass Ejection with Intricate Magnetic Structure from Multiple Active Regions - J. H. Guo; Y. W. Ni; B. Schmieder; Y. Guo; C. Xia; P. Devi; R. Chandra; S. Poedts; R. Joshi; Y. H. Zhou; H. T. Li; P. F. Chen (The Astrophysical Journal)
Coronal mass ejections (CMEs) are the eruptions of magnetized plasma from the Sun and are considered the main driver of adverse space weather events. Hence, understanding their formation process, particularly the magnetic topology, is critical for accurate space weather prediction. Here, based on imaging observations and three-dimensional (3D) data-constrained thermodynamic magnetohydrodynamic (MHD) simulation in spherical coordinates, we exhibit the birth of a CME with intricate magnetic structure from multiple active regions (ARs) due to 3D magnetic reconnection. It is observed as a coronal jet between ARs, accompanied by the back-flowing of filament materials along the jet spine after the passage of the eruptive filament. This jet connects two dimming regions within different ARs. This is an observational proxy of 3D magnetic reconnection between the CME flux rope and the null-point magnetic field lines crossing ARs. Hereafter, the thermodynamic data-constrained MHD simulation successfully reproduces the observed jet and the reconnection process that flux ropes partake in, leading to a CME flux rope with a complex magnetic structure distinct from its progenitor. The generality of this scenario is then validated by data-inspired MHD simulations in a simple multipolar magnetic configuration. This work demonstrates the role of multiple ARs in forming CMEs with intricate magnetic structures. On the one hand, a noncoherent flux rope where not all twisted magnetic field lines wind around one common axis is naturally formed. On the other hand, our findings suggest that the topology of a real CME flux rope may not be solely determined by a single AR, particularly during periods of solar maximum.